RETRACTED: The category of "linguistic personality" as a basic concept in the creation of an effective model for teaching professional speech to students of philology - Khosilova Farida; Tsoy Alla (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001